Quality, height, age and home advantage in boxing. [Calidad, altura, edad y la ventaja de boxear en casa]. - Miguel Pic (Ramón Cantó Alcaraz, 2018)
Abstract The main objective of the present study was the identification of performance indicators in boxing and their impact on the concept of home advantage (HA), among other variables. Professional boxing bouts of the European ranking were selected (N = 522), to generate 1044 units of analysis. ANOVA and T-student analyzes were applied to determine the influence of the difference between boxers in: a) quality, calculated by the number of combats won, opponent's quality, inactivity time, among other indicators; b) height and c) age, depending on the result obtained and the location of the combat. It was also used as an influential variable in the final result. By multivariate analysis (CHAID model), the quality difference between boxers was the most determinant variable (p <.000) to reach the final result, but it was also predictive regarding the combat location (p <.006). The study allowed for revealing determinant effects for the performance in boxing through the crossing of variables and analysis techniques. Suggesting coaches and boxing practitioners to do a thorough review of their training tasks based on the location of their commitments and the boxers' characteristics means they would profit the specificity of each match. The calculation of the risk percentage assumed by professional boxers to achieve success in professional boxing, is one of the practical applications of this research. Resumen El objetivo principal del presente estudio fue la identificación de indicadores de rendimiento en boxeo y su incidencia sobre el concepto de ventaja de jugar en casa (HA), entre otras variables. Fueron seleccionados combates profesionales del ranking Europeo (N=522) dando lugar a 1044 unidades de análisis. Fueron aplicados análisis ANOVA y T-student para determinar la influencia de la diferencia entre boxeadores en: a) calidad, calculada mediante el número de combates ganados, calidad del oponente, tiempo de inactividad, entre otros indicadores; b) altura y c) edad, en función del resultado obtenido y la localización del combate. También empleada esta como variable influyente en el resultado final. Mediante análisis multivariantes (modelo CHAID) la diferencia de calidad entre los boxeadores era la variable más determinante (p <.000) para alcanzar el resultado final, pero también se mostró predictiva en relación a la localización del combate (p<.006). El estudio permitió desvelar efectos determinantes para el rendimiento en boxeo mediante el cruce de variables y técnicas de análisis. Sugerir a entrenadores y practicantes de boxeo a una revisión profunda de sus tareas de entrenamiento en función de la localización de sus compromisos y las características de los boxeadores, es avanzar en la especificidad de cada combate. Calcular porcentajes de riesgo asumibles por boxeadores profesionales para conseguir éxito en boxeo profesional está entre las aplicaciones prácticas del presente estudio.